Media Influence on FMCGs - A Comparative Study among Rural and Urban Households on their Product Purchase Decision - Bhattacharjee, Abhigyan (Indian Journal of Marketing, 2011)
The media is instrumental in defining the way we think and what one's place is in the society. It has an impact on how issues are interpreted and evaluated. The term Mass Media is defined as means of communication that operate on a large scale, reaching and involving virtually everyone in the society to a greater or lesser degree (Mcquali, 2000). A medium is called mass medium when it reaches above 50 million people (Chundi and Srivastava, 2000). Thus, it essentially means dissemination of information, idea and entertainment by the communication media. Media audiences have different individual backgrounds, intelligence, interests and attitudes, which invariably influence their perceptions and interpretations about the incoming message and, therefore, the impact varies. Media has enabled people to have access to different sources of information and facilitated the people to see different people and their way of life, thus creating better ideas and perceptions about the world. The media on the one hand document endangered species, vanishing cultural heritage and life styles and activities of the past and on the other hand, it has also influenced people to accept global culture and values. In India, the Mass media primarily refers to the radio, the newspaper, cinema halls, print, television and the internet. The spread of mass media is impressive where, in the initial stage, the spread of mass media and related technology was confined largely to the urban areas and now, this has engulfed the whole society. The communication network has reached even the remote rural areas of the country. These are the main media disseminating information and serving as sources of entertainment. The primary objectives of the study are as follows: To find out the influence of mass media in product purchase decisions among the rural and urban households; To know whether there exists any significant difference or there is no significant difference between the rural and urban households in their product purchase decision (FMCGs) through the influence of mass media.